Determination Of Fracture Toughness In PBGA Packages Using Finite Element And Experimental Methods - Tan, Chew Pheng (2006)
Electronic packages especially the plastic ball grid array (PBGA) has its unique crack failure arising from the soldering process. The existence of moisture absorbed in package from ambient condition causes vapor pressure. During reflow soldering processes (215°C), the moisture absorbed vaporizes and eventually causes popcorn cracking. So, numerical method is used to characterize the fracture resistance in terms of geometric stress intensity factor (SIF). Then, the investigation of fracture toughness on epoxy molding compound (EMC) material provided boundary conditions of package cracking. In this research, Ansys software was used to simulate moisture diffusion and thermal transfer to determine the vapor pressure at the crack region. The vapor pressure loading was applied on PBGA to obtain geometric SIF using modified crack closure integral (MCCI) method. It was found that the increased in vapor pressure and higher delamination size created high geometric SIF. Load-crack edge extension relation obtained from holographic interferometry (HI) method and critical load for D.E.R. 331 as EMC material were used to evaluate fracture toughness. The fracture toughness for D.E.R 331 was found to be 0.488MPa m 1/2. Eventually, the fracture toughness for D.E.R. 331 was compared with PBGA's geometric SIF. A graph with package safety conditions was obtained. From the graph, it can be concluded that the PBGA is typically to be saved during soldering process, where vapor pressure is 1.21 MPa and delarnmatron ratio is less than 0.6. This EP's failure can be controlled through minimizing the effect of vapor pressure and reducin_g die/EMC interface delamination.